Mixed Fungal Infection (Aspergillus, Mucor, and Candida) of Severe Hand Injury. (13th March 2014) - Obradovic-Tomasev, Milana; Popovic, Aleksandra; Vuckovic, Nada; Jovanovic, Mladen
Abstract : Severe hand injuries are almost always heavily contaminated and hence wound infections in those patients are frequent. Fungal wound infections are rare in immunocompetent patients. A case of mixed fungal infection ( Aspergillus, Mucor, and Candida ) was documented in a young male patient, with a severe hand injury caused by a corn picker. The diagnosis of fungal infection was confirmed microbiologically and histopathologically. The treatment was conducted with repeated surgical necrectomy and administration of antifungal drugs according to the antimycogram. After ten weeks the patient was successfully cured. The aggressive nature of Mucor and Aspergillus skin infection was described. A high degree of suspicion and a multidisciplinary approach are necessary for an early diagnosis and the initiation of the adequate treatment. Early detection, surgical intervention, and appropriate antifungal therapy are essential in the treatment of this rare infection that could potentially lead to loss of limbs or even death.